COX-2 rs5275 and rs689466 polymorphism and risk of lung cancer: A PRISMA-compliant meta-analysis. Issue 35 (August 2018) - Li, Jiaxi; Lu, Xiaochen; Zou, Xinwei; Jiang, Yufeng; Yao, Jie; Liu, Hongtao; Ni, Bin; Ma, Haitao
Abstract: Background: Cyclooxygenase-2 (COX-2) is an inducible enzyme that mediates the synthesis of prostaglandin, which plays an important role in the inflammation response. The overexpression of COX-2 in lung cancer has been found in several studies, suggesting that COX-2 contributes to carcinogenesis. There are many previous case-control studies focused on the association between COX-2 polymorphism and lung cancer risk, however, the conclusion remained controversial. Objectives: We performed this meta-analysis to evaluate the association between COX-2 rs5275 and rs689466 polymorphism and susceptibility to lung cancer. Methods: A systematic literature research was conducted on PubMed, Embase, Cochrane Library, OVID, Web of Science, and Google Scholar up to November 30, 2017. The quality of studies was assessed by Newcastle–Ottawa scale. We combined odds ratios (ORs) and 95% confidence intervals (CIs) in 5 different genetic models for evaluation under a fixed-effect model or random-effect model. Subgroup analysis was performed according to source of control, ethnicity, pathological types, and smoking status. Sensitivity analysis and publication bias were also conducted. Results: Eventually, 14 eligible studies were included in our meta-analysis. We found rs5275 gene polymorphism decreased the risk of lung cancer under heterozygote model (OR: 0.91, 95% CI: 0.84–0.98, P  = .02). COX-2 rs689466 gene polymorphism was also related to a significantly reduced risk under allele (OR: 0.88, 95% CI: 0.82–0.95, P  = .001), homozygote (OR: 0.81, 95% CI: 0.68–0.95, P  = .01), heterozygote (OR: 0.81, 95% CI: 0.72–0.91, P  < .001), and dominant model (OR: 0.81, 95% CI: 0.72–0.91, P  < .001), except for recessive model. Subgroup analysis suggested a similar association in Asians, but not in Caucasians. Polymorphism of rs5275 was strongly associated with a reduced risk of lung adenocarcinoma according to stratified analysis by pathological types. Egger test identified no significant publication bias. Conclusions: Our meta-analysis demonstrated that COX-2 rs5275 and rs689466 polymorphism significantly decrease the risk of lung cancer in Asians but not in Caucasians, indicating COX-2 could serve as a potential diagnostic marker for lung cancer.